7y^4-25y^2+12=0 answer this question bro
Answers
Answered by
16
hay!!
Dear brother -
Given in the question
7y^4-25y²+12
Then,
=> 7y^4-21y²-3y²+12=0
=> 7y²(y²-3)-3(y²-3)=0
=>(7y²-3) (y²-3)=0
I hope it's help you
Dear brother -
Given in the question
7y^4-25y²+12
Then,
=> 7y^4-21y²-3y²+12=0
=> 7y²(y²-3)-3(y²-3)=0
=>(7y²-3) (y²-3)=0
I hope it's help you
HarishAS:
Now it is correct bro.
Answered by
8
Hi bro, Harish here.
Here is your answer:
![7y^{4} - 25 y^{2} + 12 = 0 7y^{4} - 25 y^{2} + 12 = 0](https://tex.z-dn.net/?f=7y%5E%7B4%7D+-+25+y%5E%7B2%7D+%2B+12+%3D+0)
Now, let us split -25 into -21, -4.
Then
⇒![7y^{4} - 21y^{2} -3y^{2} + 12 =0 7y^{4} - 21y^{2} -3y^{2} + 12 =0](https://tex.z-dn.net/?f=7y%5E%7B4%7D+-+21y%5E%7B2%7D+-3y%5E%7B2%7D+%2B+12+%3D0)
Now take common then,
⇒![7y^{2}(y^{2}-3)-3(y^{2}-3) = 0 7y^{2}(y^{2}-3)-3(y^{2}-3) = 0](https://tex.z-dn.net/?f=7y%5E%7B2%7D%28y%5E%7B2%7D-3%29-3%28y%5E%7B2%7D-3%29+%3D+0)
⇒![(7y^{2} -3) (y^{2}-3) =0 (7y^{2} -3) (y^{2}-3) =0](https://tex.z-dn.net/?f=%287y%5E%7B2%7D+-3%29+%28y%5E%7B2%7D-3%29+%3D0)
__________________________________________________
Hope my answer is helpful to you.
Here is your answer:
Now, let us split -25 into -21, -4.
Then
⇒
Now take common then,
⇒
⇒
__________________________________________________
Hope my answer is helpful to you.
Similar questions